Application of Wordwall Interactive Media to Increase Student Activity in Social Studies Learning at SBSM 5 Gombak, Malaysia - Hikmah Wifaqi (Program Studi Pendidikan IPS Unesa, 2025)
This research aims to analyze the effectiveness of the use of interactive media Wordwall in increasing student activeness in the subject of Social Knowledge (IPS) at Sungai Mulia Guidance Studio 5 Gombak, Malaysia. Using Classroom Action Research (PTK) method in two cycles, each cycle consists of planning, implementation, observation, and reflection stages. The research subjects were 19 6th grade students. In the first cycle, the Wordwall